Northrop Frye and Others : Interpenetrating Visions - Denham, Robert D (Book collections on Project MUSE., 2015)
"This collection of essays considers Northrop Frye's criticism in relation to twelve figures in the history of Western culture, some lesser-known, even obscure, who influenced his thinking in various ways but about whom he never wrote anything extensive. The impetus for the book goes back to my editing of Frye's Late Notebooks, where I ran across his proclamation that Henry Reynolds was "the greatest critic before Johnson." I could not recall ever having encountered the name Henry Reynolds either in the histories of criticism or in the anthologies of critical texts. But with the Collected Works of Frye now in print it became possible to track down all of the references to Reynolds in Frye's published as well as his previously unpublished writing. I surmised that if we were to have before us everything Frye wrote about Reynolds, then perhaps we could begin to understand the attraction Reynolds held for him. The references to Reynolds turned out to be rather meager (only six), but they were sufficient for me to draw several conclusions about Frye's interest in Reynolds. So the question that motivated this essay was why Frye would lavish such a superlative upon an obscure seventeenth century writer about whom we know almost nothing. The resulting essay shows how Reynolds and Frye are linked by their joint interest in allegory, poetic etymology, and something quite akin to Longinian ekstasis. As I became more familiar with Frye's previously unpublished work, other figures important to Frye's thinking began to emerge, including Bruno, Joachim of Floris, Burton, Kierkegaard, Frances Yates--writers to whom he had not devoted separate books or essays, as he had done in the case of Blake, Shakespeare, Milton, Dickinson, Keats, Shelley, Eliot, Joyce, Yeats, Stevens, the Bible, and Spengler, among others. The twelve "others" eventually came to represent a space occupied by writers whose interests paralleled Frye's and helped to establish his own critical universe."--